Cross Breeding and Hybrid Identification of Sulphite-tolerant Hybrids of Saccharomyces uvarum - Liu, X.Z.; Zhang, Z.M.; Zhang, H.Y. (South African Journal of Enology and Viticulture, 2017)
Yeast species belonging to Saccharomyces have great potential for the wine industry. However, the sulphite tolerance of most S. uvarum strains is quite poor compared with that of the other Saccharomyces strains. In order to get new S. uvarum strains with tolerance to sulphite, and also with good fermentation characteristics, 21 candidates were screened from three different crossing combinations of sensitive S. uvarum strains to one sulphitetolerant strain. Ten of these hybrids were sulphite tolerant and contained the FZF1 gene from both parents. Intersimple sequence repeat (ISSR) analysis confirmed their hybrid status, based on six primers that produced 55 clear and reproducible bands, including 32 that were polymorphic. Two hybrids had identical fingerprints, indicating that it was the same clone. Thus, nine different novel sulphite-resistant hybrids of S. uvarum were obtained. The selected hybrid strains fermented very well at 30ºC in Sauvignon Blanc grape juice containing 2 mM of sodium sulphite, with minor differences in fermentation performance. Two strains (namely C13 and C21) performed very similarly to the sulphite-tolerant parent A9 and a commercial S. cerevisiae strain EC1118, and the production of fermentation aromas, namely propanol, isobutanol and isoamyl alcohol by C13 was found to be the highest. This is the first report of using hybridisation to breed the sulphite-tolerant S. uvarum strains.